Desain Sistem Pengadaan Bahan Baku Berkelanjutan pada Produk Makanan - Karina Fitriani; Elisa Kusrini; Hartomo Soewardi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to design a sustainable raw material procurement system for SMEs producing fish based food products, particularly otak-otak processors in Tanjungpinang, in response to declining fish supply and production instability that threaten business continuity. A quantitative descriptive approach was applied through benchmarking and SEM-PLS analysis to identify the most influential economic, social, and environmental factors in shaping the system design, referring to LKPP Regulation No. 157 of 2024. Data were obtained from 40 SMEs using questionnaires, interviews, and field observations. The results show that economic elements such as life cycle costing and production planning remain weak and therefore need to become priority components in the system design. In contrast, social and environmental dimensions perform well, particularly in community involvement, waste management, and eco friendly packaging, making them a strong foundation for developing the system. The analysis also highlights green suppliers and alternative sourcing as critical gaps that require strengthening through supplier evaluation mechanisms, long-term partnerships, and supply diversification. Based on these results, the study formulates a sustainable procurement system that aligns supplier selection, raw material planning, and environmental social compliance into one integrated framework. The design emphasizes clear procurement standards, measurable supplier performance indicators, and structured collaboration within the supply chain to secure raw material availability while minimizing environmental and social risks. This system provides a practical roadmap for SMEs to shift from reactive purchasing to strategic and sustainability-driven procurement, strengthening operational resilience and long term business viability.